Microstructure, Thermal, and Magnetic Properties of the AlCoFeMnNi and AlCoFeMnNiX10 (X = Ti, Cr, Sn, V, Hf, Ga) High-Entropy Alloys - Ibrahim, Pshdar Ahmed; Canbay, Canan Aksu; Ozkul, Iskender (Springer, 2022)
The first generation of high-entropy alloys (HEAs) has five or more equiatomic components fabricated together in the concentration of 5-35 at.%. Recently, the second generation of HEAs was identified as having non-equimolar compositions. HEAs have excellent mechanical properties and magnetic behavior that may vary with the doping of other alloying elements. In the current study, various components (Ti, Cr, Sn, V, Hf, Ga) were added to an equiatomic AlCoFeMnNi alloy, and then the microstructure, thermal and magnetic properties of the alloys were investigated. As a result, all samples showed ferromagnetic behavior, and the highest value of magnetization was found in the AlCoFeMnNi alloy (141.1 emu/g). In comparison, the lowest value (51.2 emu/g) was detected through Hf addition to the AlCoFeMnNi alloy. Therefore, the change in magnetic characteristics is due to the phase change related to different element additions. In addition, the calculated coercivity for the tested alloys was in the range of 78-325 Oe, which means that the produced alloys have semi-hard magnetic behavior.
Keywords: Microstructure; Magnetic properties; High-entropy alloy (HEA); Coercivity; DTA; XRD